Editorial - Madjid Tavana (Decision Analytics, 2014)
Decision making is a balancing act on a three-legged stool of insight, analysis, and action. If we cannot keep the three legs even, we wobble. And sitting on the stool is not even enough. We have to juggle known with unknown, fact with fiction, cognition with sensation and knowledge with ignorance. To make informed and effective decisions, decision makers must keep the three legs of insight, analysis, and action even by embracing: Data Mining - to leverage the knowledge hidden within organizational data by utilizing a wide range of statistical methods, data visualization techniques, and pattern recognition approaches. Predictive Modeling - to identify organizational risks and opportunities by exploiting patterns found in historical and transactional data. Simulation Modeling - to examine and compare options and scenarios prior to implementation by utilizing application of simulation in enterprise and organizational context. Optimization Modeling - to make the best choice by means of various optimization models. Prescriptive Methods - to create better solutions by exploiting the joint application of predictive models and optimization technology. Business Intelligence - to gain and sustain a competitive edge by utilizing the latest techniques in data mining, analysis, and performance management.
Keywords: 330